Optimizing the level of disaster preparedness for coastal children in creating a disaster resilient generation - Rismawan Adi Yunanto; Ruris Haristiani; Baskoro Setioputro; Dewi Rokhmah (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Indonesia is home to various natural disasters, including earthquakes and tsunamis, due to its location in the Ring of Fire. Jember Regency in East Java is one of the areas with a high risk of these disasters. Sabrang Village, bordering the South Coast of Jember, has the potential to become a disaster-resilient village. This program aims to increase disaster preparedness for children on the south coast, optimize partner empowerment in increasing child preparedness, and establish a Disaster Empowerment Center (DEC) in Sabrang Village. The DEC program was implemented over three months, involving coastal children. Methods included education, training, and empowerment through Communication, Information, and Education (IEC) and disaster simulation training. Program evaluation used a preparedness questionnaire covering participants' knowledge, attitudes, and skills. The DEC program succeeded in increasing disaster preparedness for children in Sabrang Village. Collaboration with the village government, public health center, and other partners was crucial to the program's success. DEC implementation can serve as a model for community empowerment in dealing with earthquakes and tsunamis.